Mesoporous ZnCo2O4 microspheres as an anode material for high-performance secondary lithium ion batteries. Issue 25 (21st March 2015) - Guo, Lingyun; Ru, Qiang; Song, Xiong; Hu, Shejun; Mo, Yudi
<x xml:space="preserve">Abstract</x> The as-prepared mesoporous ZnCo2O4 microspheres showed a high specific capacity and excellent electrochemical performance when used as an anode material for lithium ion batteries.